L'impronta della "scuola di Milano" sulla Casa della Cultura (Materiali di Estetica. Terza serie, 2022)
The philosophical cenacle gathered around Antonio Banfi was the undisputed protagonist of the first decades of Casa della Cultura in Milan. But even in subsequent seasons, until today, traces of a cultural heritage that has proved particularly fruitful can be easily grasped
Keywords: Casa della Cultura; Scuola di Milano; Antonio Banfi